Case report: VEXAS syndrome and literature review - Jones, Can; Ivanov, Stanislav; Ferraro, Pablo; Younes, Souhad; Fernandez, Hugo (Frontiers in Hematology, 2024)
VEXAS syndrome (Vacuoles, E1 enzyme, X-linked, Autoinflammatory, Somatic) is a novel disorder first described in 2020. Patients are diagnosed by identifying a somatic mutation of the ubiquitin-like modifier-activating enzyme 1 (UBA1) gene. They usually have systemic inflammation and present with a combination of hematologic and rheumatologic abnormalities such as myelodysplastic syndrome and polychondritis. VEXAS syndrome patients are at increased risk of developing hematologic malignancies. We present a case of a 60-year-old male who developed transfusion-dependent macrocytic anemia, was found to have UBA1 mutation in the bone marrow, and was diagnosed with VEXAS syndrome. The patient responded well to steroid treatment and did not require more blood transfusion. The two main goals of treating VEXAS syndrome are eradicating the UBA1 mutated hematopoietic cells and inhibiting the inflammatory process. Early stem cell transplant evaluation is necessary as VEXAS-related complications may limit the efficacy of transplantation. Further research is required to improve the prognosis and quality of life of VEXAS syndrome patients.